A Review on Neutrino Oscillation Probabilities and Sterile Neutrinos - Kendra Jean-Jacques; Anna Roland; Christelle Billan; Preet Sharma (Ital Publication, 2022)
In the past decades, there have been many groundbreaking discoveries and advancements in the field of particle physics. One of the important elementary breakthroughs is the phenomenology of neutrino oscillations. This includes the properties of neutrinos in the Standard Model (SM) and how neutrino oscillations and their properties have been so important in strengthening the SM. Neutrino oscillations also play a vital role in understanding the current nature of our Universe and the way it behaves. There is also a great interest in neutrino oscillations and their connection with dark matter. In this review, we start with the introduction and discuss the theoretical background of neutrino oscillations and some experiments, which are working to detect the properties of neutrinos. Then the fundamentals of neutrino oscillations and their interactions were described. Since there are multiple sources of neutrinos, we have described the three sectors through which we can expect neutrinos to be produced. These are the atmospheric, solar, and reactor sectors. A brief section on the important milestones in neutrino oscillations is included because of the experiments and what they use to detect neutrino properties. Finally, we also include a section on sterile neutrinos since they have been under study for a long time and there is a possibility of them being connected to dark matter interactions. Doi: 10.28991/ESJ-2022-06-02-015 Full Text: PDF